Penerapan Model Pembelajaran Kooperatif Tipe Jigsaw Untuk Meningkatkan Prestasi Belajar Ekonomi Kelas XI MIPA 2 di SMA Negeri 1 Sawan Tahun Pelajaran 2020/2021 - L.H.K. Dewi; I.G.K.A. Sunu; I.N. Natajaya (Jurnal Administrasi Pendidikan Indonesia, 2021)
This study aims to improve students' economic learning outcomes through the application of the Jigsaw type cooperative learning model. This research is a classroom action research involving 35 students of XI Mipa 2 totaling 35 people at SMA Negeri 1 Sawan. The data collection method is a test of learning outcomes that are assessed based on responses to the google form question link and the assessment rubric of group discussions. The data analysis technique used is descriptive statistical quantitative data analysis by looking for the average, absorption, classical completeness of class learning outcomes. The results obtained from this study are the application of the Jigsaw type cooperative learning model can improve student learning outcomes in economics subjects. This is evident from the results obtained in the initial state the average learning achievement is 60.49 with 25.71% learning completeness and in the first cycle it reaches an average value of 72.79 with 82.86% learning mastery and in the second cycle it reaches an average value. an average of 80.46 with 100% learning completeness. The conclusion obtained from this study is that the application of the Jigsaw type cooperative learning model can improve economic learning achievement for class XI Mipa 2 at SMA Negeri 1 Sawan in the 2020/2021 academic year.